Demand forecasting for distribution transformer load management - Cabling, Aniano C. (2001)
Distribution transformers represent a substantial proportion of the electric system investment. As such, transformers failures generate equivalent economic losses for the electric utility and its customers. Accurately determining the demands of all distribution transformers in service is therefore vital for the efficient management of distribution transformers. This thesis presents a method of forecasting distribution transformer demand to be used in transformer load monitoring system. Forecasting equations for distribution transformers serving residential, commercial and mixed customers were derived from customer billing data. Unmetered components of energy consumption such as technical loss, streetlights consumption and non-technical losses like electricity theft and pilferage were also considered in the development of forecasting equations.